Prevalence of malaria, anemia and associated factors among school children in Hawassa city, Sidama, Ethiopia. - Alia Gena; Solomon Asnake; Tadesse Menjetta (PLoS ONE)
Background The recurrent occurrence of malaria and anemia are leading causes of morbidity and mortality in children especially in sub-Saharan Africa. In tropical regions, malaria is a major contributor to anemia which occurs due to reduced hemoglobin levels caused by hemolysis of infected and uninfected red blood cells and as a result bone marrow dyserythropoiesis. Though malaria and anemia are two interlinked health problems among school children, there is scarce information about the issue in the study area. Hence the current study aimed to assess the prevalence of malaria and anemia and associated factors among school children in Hawassa City, Sidama, Ethiopia. Method A cross-sectional study was conducted from April to June 2024 in selected public primary schools in Hawassa City, recruiting 329 children. Socio-demographic data were collected using a pretested questionnaire. Thick and thin blood films were prepared for microscopic examination of malaria parasites, and parasite counts were conducted. A rapid diagnostic test was also performed for malaria diagnosis. A digital hemoglobinometer was used to determine hemoglobin levels and assess anemia prevalence. Data were analyzed using SPSS version 27, with bivariate and multivariate logistic regression performed. The strength of association was determined by computing adjusted odds ratios with 95% confidence intervals, and a p-value of <0.05 was considered statistically significant. Result Malaria and anemia were present in 8.5% and 9.4% of the children, respectively while, 29% of anemic children were also infected by malaria. The odds of having anemia were highest in children with malaria (AOR = 4.983, 95% CI: 1.067-23.265), previous history of malaria (AOR = 9.121, 95% CI: 1.686-49.336). Using insecticide treated-net (AOR = 0.024, 95% CI: 0.001-0.755), knowledge of malaria transmission (AOR = 0.205, 95% CI: 0.049-0.854),has significantly reduced malaria risk, highlighting the role of preventive practices and awareness. Meal frequency (AOR = 6.243, 95% CI: 1.956-19.923), malaria infection (AOR = 13.258, 95% CI: 3.188-55.139), and history of wasting (AOR = 5.760, 95% CI: 2.059-16.112) were identified as significant risk factors of anemia. Conclusion This study found that 8.5% of school children in Hawassa City had malaria and 9.4% were anemic, indicating a mild public health concern. A strong association was observed between the two conditions: malaria-infected children were over 13 times more likely to be anemic. These findings highlight the need for integrated malaria prevention and nutrition programs. Interventions should focus on ITN use, improving dietary practices, and identifying asymptomatic malaria carriers to reduce the burden of both diseases.